Les relations entre jardins et paysages, dans les récits des voyageurs français en Espagne - Agnès Juvanon du Vachat (Projets de Paysage)
This article analyses the connections between the gardens and landscapes in the French travel writings in Spain from the 17th to the 19th century. It reveals that these two spaces do not exclude one another but make sense in a dynamic pattern. Moreover, the trip, as a sensitive and moving approach, allows us to grab this dynamic relationship.